Volcano - Moritz, Neal H.; Armstrong, Jerome; Jackson, Mick, 1960-; Jones, Tommy Lee, 1946-; Heche, Anne; Hoffmann, Gaby, 1982-; Cheadle, Don; David, Keith; Twentieth Century-Fox Film Corporation; Anchor Bay Entertainment, Inc. (Century City, Los Angeles, California Twentieth Century Fox, 2013)
A volcano erupts in Los Angeles and destroys everything in its path.
Title from disc surface.
Originally released as a motion picture in 1997.
Director of photography, Theo van de Sande ; editor, Michael Tronick, Don Brochu ; music, Alan Silvestri.
Tommy Lee Jones, Anne Heche, Gaby Hoffmann, Don Cheadle, Keith David.
Rating: PG-13; for intense depiction of urban disaster and related injuries; CHV rating: PG.
DVD, region 1, anamorphic widescreen (1.85:1) presentation; Dolby Digital 5.1.
Keywords: Volcanic eruptions -- California -- Los Angeles -- Drama; Volcanic eruptions; California -- Los Angeles; Video recordings for the hearing impaired; Feature films; Action and adventure films; Drama